(untitled) (SCIÉNDO INGENIUM, 2023)
In this work, the 2D Convection - Diffusion equation was used to model the process of contaminant transport by convection and diffusion. In particular, we assume that we are modeling this pollutant transport process in shallow water and with a unidirectional flow movement in the convective part. The diffusion coefficient is considered constant and depends only on the nature of the substance, a value of 0.004 has been considered. Finite difference numerical schemes are applied to a domain in the XY plane, with side 1. The developed numerical model could be used to predict the distribution of polluting material. The value of the diffusion coefficient strongly influences the step size in time (dt) and the speed values ​​that we give to the convective flow. A faster movement of the contaminant in the direction of the resultant of the convective flow was appreciated, as well as a decrease in the speed of the diffusion process when the local concentration levels decreased and therefore moving only by convection.